(untitled) (Anuario Filosófico, 2018)
In the Anthropology, the person has a self-organizing communicative structure, so person cannot be unique, lonely. This has been called by Polo: «Coexistence». It shows that the «Díada» (Duality) is richness, plenitude (fullness). This makes possible to mark the difference between two complementary person’s types: the male person and the female person. They could be called: «coexistence-from» and «coexistence-in».